Comparative analysis of peak impact acceleration and impact shock frequency components according to the type of treadmill for treadmill-running - Lee, J. S.; Hur, S. E.; Park, S. H.; Moon, H. W.; Koo, B. H. (Korean Journal of Sport Biomechanics, 2017)
Objective: The purpose of this study was to show differences in impact variables between treadmills with (treadmills B, C, and D) and treadmills without a shock-absorbing function (treadmill A) to propose the development of a treadmill with improved or added shock-absorbing function to reduce impact shock. Method: Thirteen male students in their twenties who had habitual rear foot strike during running ran on four treadmills at 2.67 m/sec while ankle and neck acceleration data were collected. The magnitude of the ankle and neck acceleration peaks and peak positive ankle acceleration were calculated. The power spectral density of each signal was calculated to transform the ankle and neck accelerations in the frequency domain. Results: The peak positive ankle acceleration on treadmill B was significantly lesser than that on treadmills A and D, and that on treadmill C was significantly less than that on treadmill A (p < .01). Peak positive neck acceleration was not statistically different between the treadmills. The frequencies of the peak power of the ankle and neck acceleration signal within the lower and higher frequency ranges were not statistically different between the treadmills. The signal power magnitude of the ankle in higher frequency ranges on treadmill B was significantly less than that on treadmills A, C, and D (p < .01). The signal power magnitude of the ankle in higher frequency ranges was not statistically different between the treadmills. The signal power magnitudes of the neck acceleration signal within the lower and higher frequency ranges were not statistically significantly different between the treadmills. Conclusion: Our results indicate that the shock-absorbing function of a treadmill plays a role in reducing impact shock. Therefore, in future treadmill development, shock-absorbing function should be improved or incorporated to reduce impact shock to the body.